2022
DOI: 10.1186/s13054-022-04157-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nutrition issues in 2022: What is missing to trust supplemental parenteral nutrition (SPN) in ICU patients?

Abstract: A multidisciplinary group of international physicians involved in the medical nutrition therapy (MNT) of adult critically ill patients met to discuss the value, role, and open questions regarding supplemental parenteral nutrition (SPN) along with oral or enteral nutrition (EN), particularly in the intensive care unit (ICU) setting. This manuscript summarizes the discussions and results to highlight the importance of SPN as part of a comprehensive approach to MNT in critically ill adults and for researchers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The actual dosages administered were the same or slightly higher in the IC group, but were slightly lower in the estimating formula group [11,32,33,35]. Berger et al reported that the risk of nutrient overdosage without IC creates a barrier to the administration of enteral nutrition [39]. The control group may have been hesitant to use aggressive nutritional therapy due to uncertainty regarding the calculated REE.…”
Section: Discussionmentioning
confidence: 96%
“…The actual dosages administered were the same or slightly higher in the IC group, but were slightly lower in the estimating formula group [11,32,33,35]. Berger et al reported that the risk of nutrient overdosage without IC creates a barrier to the administration of enteral nutrition [39]. The control group may have been hesitant to use aggressive nutritional therapy due to uncertainty regarding the calculated REE.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are key factors and times when PN should be considered in the modern MCS era (e.g. pre-existing malnutrition, persistent hemodynamic instability, EN intolerance, failure to reach energy and nutrient targets) to improve nutrient delivery, especially in the first few ICU weeks or acute phase when historically majority of calorie/protein deficits are created [31 ▪▪ ,32 ▪ ].…”
Section: Nutrition Routementioning
confidence: 99%
“…EL entails vitamin deficiencies that require supplementation, and thus vitamins are administered as a commercial multivitamin supplement composed of vitamins C, A, E, K and the B complex (B 1 , B 2 , B 3 , B 6 , B 7 , B 9 , B 12 ) [ 79 ]. The literature includes a series of considerations with respect to SPN and vitamins: (a) there is no conclusive evidence of or studies on the possible benefit of vitamin D, although there are studies that associate it with a decrease in mortality and mechanical ventilation time; (b) vitamin C is unstable, susceptible to oxidation reactions and is usually associated with neuropathy, hemolysis and hyperglycemia phenomena [ 80 , 81 ]; (c) B group vitamins are involved in reducing fatigue syndrome [ 82 ]; (d) vitamin supplementation is justified in terms of nutritional requirements to improve immune function, regulate hypercatabolism and exert an antioxidant action, but if it is provided too early, it can have adverse effects such as prolonging the ICU stay and the risk of infections [ 83 ]; (e) ASPEN and ESPEN clinical practice guidelines refer to the need to supplement PN with vitamins in critical condition, but there is no consensus or evidence on timing, clinical criteria or protocols in EL [ 84 ].…”
Section: Supplements Of Interest For Parenteral Nutrition Formulationsmentioning
confidence: 99%